Low‐dose aspirin improves blood perfusion of endometrium of unexplained recurrent biochemical pregnancy loss. Issue 2 (6th August 2021) - Zhang, Xiaoxin; Guo, Feng; Wang, Qiaohong; Bai, Wenxin; Zhao, Aimin
Abstract: Objective: To assess the differences in Doppler parameters of endometrial receptivity in unexplained recurrent biochemical pregnancy loss (URBPL) and the therapeutic effect of low‐dose aspirin (LDA). Methods: A retrospective study was conducted at Ren Ji Hospital, Shanghai, PR China, from January 2017 to January 2019. Doppler parameters of endometrium and uterus were recorded as the evaluation of the endometrial receptivity. Receiver operating characteristic (ROC) curve was managed to predict the risk of URBPL. Ultrasonography tests were repeated after 2 months of treatment with LDA. Results: Biochemical pregnancies did not correlate with maternal age. The resistance of endometrial perfusion (pulsatility index, resistive index, and systolic‐to‐diastolic ratio) was significantly higher in URBPLs ( P  < 0.001) and had predictive values (0.739, 0.779, and 0.760, respectively). Endometrial thickness and impedance to uterine blood flow showed no statistically significant difference ( P  > 0.05). After treatment with LDA, patients with URBPL improved the blood perfusion of endometrium significantly ( P  < 0.01). Conclusion: There was no relation between BPL and maternal age. Patients with URBPL had inappropriate endometrial blood velocity. Doppler indices are capable of predicting the risk of URBPL. LDA exerts the therapeutic effect on improving blood perfusion of endometrium in URBPL. Abstract : Biochemical pregnancy loss is not related to maternal age. Patients with unexplained recurrent biochemical pregnancy loss had inappropriate endometrial blood velocity, and low‐dose aspirin could improve blood perfusion of endometrium.